please tell me the answer
Attachments:
![](https://hi-static.z-dn.net/files/d84/eca8a845e6e0d4e4bdeeb4e9f29662b4.jpg)
Answers
Answered by
2
Hey
Here is your answer,
Solution :
Given that,
3+√7 / 3-√7 = a+b√7
First , let's simplify LHS.
LHS = 3+√7/3-√7 x 3+√7/3+√7
= (3+√7)^2 / (3)^2 - (√7)^2
= 9+7+6√7 / 9-7
= 16 + 6√7 / 2
= 2 (8+3√7)/2
= 8+3√7
= a+b√7
Therefore , a = 8 and b = 3
Hope it helps you!
Here is your answer,
Solution :
Given that,
3+√7 / 3-√7 = a+b√7
First , let's simplify LHS.
LHS = 3+√7/3-√7 x 3+√7/3+√7
= (3+√7)^2 / (3)^2 - (√7)^2
= 9+7+6√7 / 9-7
= 16 + 6√7 / 2
= 2 (8+3√7)/2
= 8+3√7
= a+b√7
Therefore , a = 8 and b = 3
Hope it helps you!
mucho:
marked
Similar questions